The Association between Skipping Breakfast and Biochemical Variables in Sedentary Obese Children and Adolescents - Freitas Junior, Ismael F. [UNESP]; Christofaro, Diego G. D. [UNESP]; Codogno, Jamile S. [UNESP]; Monteiro, Paula A. [UNESP]; Silveira, Loreana S. [UNESP]; Fernandes, Romulo A. [UNESP] (Mosby-elsevier, 2012)
Objective To investigate the relationship between skipping meals and biochemical variables in obese children and adolescents.Study design The sample was composed of 174 obese children and adolescents, aged between 6 and 16 years (80 male and 94 female). Body composition was assessed by dual-energy x-ray absorptiometry, fasting blood glucose, and lipid profile were measured after 12 hours fasting. The frequency of skipping breakfast, lunch, or dinner was assessed through a face-to-face interview carried out with the parents.Results The prevalence of eating breakfast daily was low in boys (47.5%) and girls (44.7%). A higher frequency of eating breakfast was negatively correlated with glucose (r = -0.16; P = .026), triglycerides (r = -0.19; P = .011), and very low density lipoprotein cholesterol (r = -0.21; P = .005). In the multivariate model, the weekly frequency of eating breakfast remained negatively associated with glucose (beta = -0.975; P = .017), triglycerides (beta = -7.792; P = .017), and very low density lipoprotein cholesterol (beta = -1.870; P = .009) independent of age, sex, trunk fatness, and parents' education.Conclusion Skipping meals, mainly breakfast, is associated with glucose and lipid levels in obese children and adolescents. (J Pediatr 2012;161:871-4).